Process R&D in Monopoly under Demand Uncertainty - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
I investigate R&D efforts for process innovation in a monopoly with uncertain demand. Two different models are proposed, where either (i) the reservation price is affected by an additive shock and the marginal production cost is increasing, or (ii) a multiplicative shock on the slope of demand combines with a flat marginal production cost. In either case, price-setting behaviour generates a larger R&D investment than quantity-setting behaviour. An Arrowian interpretation of the first result and a Schumpeterian interpretation of the second are proposed.
Keywords: 330; Technischer Fortschritt; Forschung; Monopol; Theorie